Compatibility and stability of pertuzumab and trastuzumab admixtures in i.v. infusion bags for coadministration. Issue 3 (5th December 2012) - Kwong Glover, Zephania W.; Gennaro, Lynn; Yadav, Sandeep; Demeule, Barthélemy; Wong, Pin Yee; Sreedhara, Alavattam
Abstract The physical/chemical stability and potential interactions after diluting two immunoglobulin G1 monoclonal antibodies (mAb), pertuzumab (Perjeta®) and trastuzumab (Herceptin®), in a single intravenous (i.v.) infusion bag containing 0.9% saline (NaCl) solution was evaluated. As commercial products, pertuzumab and trastuzumab are administered through i.v. infusion to patients sequentially, that is, one drug after the other. To increase convenience and minimize the in‐clinic time for patients, the compatibility of coadministering pertuzumab (420 and 840 mg) mixed with either 420 or 720 mg trastuzumab, respectively, in a single 250 mL polyolefin or polyvinyl chloride i.v. bag stored for up to 24 h at 5°C or 30°C was determined. The controls (i.e., pertuzumab alone in an i.v. bag, trastuzumab alone in an i.v. bag) and the mAb mixture were assessed using color, appearance, and clarity, concentration and turbidity by ultraviolet spectroscopy, particulate analysis by light obscuration, size‐exclusion chromatography, capillary electrophoresis‐sodium dodecyl sulfate, analytical ultracentrifugation, and ion‐exchange chromatography. Additionally, capillary zone electrophoresis, imaged capillary isoelectric focusing, and potency were utilized to measure the stability of the admixtures containing 1:1 mixtures of pertuzumab/trastuzumab and their respective controls (420 mg pertuzumab alone and 420 mg trastuzumab alone). No observable differences were detected by the above methods in the pertuzumab/trastuzumab mixtures stored up to 24 h at either 5°C or 30°C. The physicochemical methods as listed above were able to detect both molecules as well as the minor variants in the drug mixture, even though some overlap of mAb species were seen in the chromatograms and electropherograms. Furthermore, biophysical analysis also did not show any interactions between the two mAbs or any physical instability under these conditions. Additionally, the drug mixture tested by the pertuzumab‐specific inhibition of cell proliferation bioassay showed comparable potency before and after storage. On the basis of these results, pertuzumab and trastuzumab admixture in a single i.v. bag is physically and chemically stable for up to 24 h at 5°C or 30°C and can be used for clinical administration. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:794–812, 2013